Thyroid Circadian Timing: Roles in Physiology and Thyroid Malignancies. (April 2015) - Philippe, Jacques; Dibner, Charna
The circadian clock represents an anticipatory mechanism, well preserved in evolution. It has a critical impact on most aspects of the physiology of light-sensitive organisms. These rhythmic processes are governed by environmental cues (fluctuations in light intensity and temperature), an internal circadian timing system, and interactions between this timekeeping system and environmental signals. Endocrine body rhythms, including hypothalamic-pituitary-thyroid (HPT) axis rhythms, are tightly regulated by the circadian system. Although the circadian profiles of thyroid-releasing hormone (TRH), thyroid-stimulating hormone (TSH), thyroxine (T4), and triiodothyronine (T3) in blood have been well described, relatively few studies have analyzed molecular mechanisms governing the circadian regulation of HPT axis function. In this review, we will discuss the latest findings in the area of complex regulation of thyroid gland function by the circadian oscillator. We will also highlight the molecular makeup of the human thyroid oscillator as well as the potential link between thyroid malignant transformation and alterations in the clockwork.